I could only figure out the partial quotient way im sorry but i think this could help
The answer for 5+(-3) is 2
Answer: x+6
Step-by-step explanation:
5x-3(x-2)-x .......................... Question
5x-3x+6-x ........................... Distribute
1x+6 ..................................... Combine like terms
x+6 ...................................... Multiply by 1
Plug 8 for y
8 = 2x + 4
Subtract 4
4 = 2x
Divide by 2
x = 2
Plug 16 for y
16 = 2x + 4
Subtract by 4
12 = 2x
Divide by 2
x = 6
Substitute 20 for y
20 = 2x + 4
16 = 2x
x = 8
Substitute 22 for y
22 = 2x + 4
18 = 2x
9 = x
So the values are 2, 6, 8, 9
Answer:
-17 =s
Step-by-step explanation:
-8s +4 = -7s +21
Add 8s to each side
-8s+8s +4 = -7s+8s +21
4 = s+21
Subtract 21 from each side
4-21 = s+21-21
-17 =s